Morphological integration versus ecological plasticity in the avian pelvic limb skeleton. (5th January 2013) - Stoessel, Alexander; Kilbourne, Brandon M.; Fischer, Martin S.
Abstract Understanding patterns and distributions of morphological traits is essential for discerning underpinning processes of morphological variation. We report on the variation in the avian pelvic limb skeleton. Length and width variables were measured in the skeletons of 236 avian species in order to examine the importance of body mass, ecological factors, phylogeny and integration in the formation of specific hindlimb morphology. Scaling relationships with body mass were analyzed across Aves and in individual avian subclades. Principal component analysis and multiple regressions were performed to examine the relationship between morphology, ecology, and phylogeny. Finally, the occurrence of within‐limb morphological integration was tested by partial correlation analysis of the residuals from element lengths vs. body mass and correlation analysis of avian hindlimb proportions. Body mass is the greatest contributor to variation, and it strongly influences variation in avian skeletal lengths. Lengthening of the leg typically comes from disproportionate increases in tibiotarsal and tarsometatarsal length. Partial correlation analysis showed that only these two elements are distinctly integrated consistently across all bird taxa, whereas relation of femur and third toe to other limb elements displays no clear pattern. Hence, morphological integration of all elements is not a prerequisite for limb design, and variation between taxa is mainly to be found in femoral and digital length. Furthermore, variation in tibiotarsal relative length is much lower than in other elements likely due to geometric constrains. Clear ecological adaptations are obscured by multifunctionality of the avian hindlimb, and phylogeny significantly constrains the morphology. Finally, when looking at relative lengths segmented limbs meet the requirements of many‐to‐one‐mapping of phenotype to functional property, in line with a common concept of evolvability of function and morphology. J. Morphol., 2013. © 2013 Wiley Periodicals, Inc.